Travel Bubble Policy in Indonesia: Opportunities and Challenges - Barsei, Adhityo Nugraha (UIN Sunan Ampel Surabaya, 2022)
The COVID-19 pandemic has hurt the world economy. The tourism industry of Indonesia was the most sector affected by the air travel restrictions policy during the COVID-19 era. After the first wave of COVID-19 moved slowly, several countries began to think about how to recover their economy through travel arrangements. The term travel bubble is increasingly popular to revive the economy through cooperation in the tourism sector between countries. Indonesia has launched travel bubble arrangement in Batam and Bintan with Singapore in January, 2022. This study aims to analyze the opportunities and challenges of the Travel Bubble policy in Indonesia. Data collection techniques used secondary data such as documentation and literature study. Data analysis was carried out in three stages, namely condensing data, displaying data, verifying data, and drawing conclusions. The results of this study are opportunities and challenges related to the application of the travel bubble in Indonesia. The opportunities are (1) travel bubble able to increase tourism activities, (2) travel bubble has had success in island-based countries, (3) travel bubble procedure suitable to be tested and adopted, and (4) as momentum for cooperation with neighboring countries. Then the challenges are (1) public sentiment related to the increase in covid cases, (2) there are travel anxiety to travel to Indonesia rank in transmission COVID-19 cases, (3) the opinion of epidemiologists regarding the variants and waves of covid, and (4) the difficulty of collaborating with neighboring countries. Keywords: travel bubble, tourism, foreign tourists, economic recovery.